Efektifitas Undang-Undang No 8 Tahun 1999 Dalam Menjamin Hak Konsumen Atas Keamanan Produk Makanan Olahan - Sri Agustini; Widya Yoseva; Irdiwan Irdiwan; Peri Fernando (Journal of Global Legal Review, 2025)
The effectiveness of Law Number 8 of 1999 on Consumer Protection in ensuring consumers’ rights to the safety of processed food products remains a critical legal issue in Indonesia. Despite the existence of a comprehensive regulatory framework and the supervisory role of the National Agency of Drug and Food Control (BPOM), violations related to unsafe processed food products continue to occur. This study aims to analyze the effectiveness of Law Number 8 of 1999 in guaranteeing consumers’ rights to the safety of processed food products, as well as to identify the legal and institutional obstacles that hinder effective law enforcement. This research employs a normative juridical method with a statutory approach, supported by case studies of food safety violations and secondary data from BPOM reports. The findings indicate that the effectiveness of the Consumer Protection Law is constrained by weak supervision, limited institutional capacity, low compliance among business actors, ineffective legal sanctions, and inadequate consumer legal awareness. From a theoretical perspective, these conditions reflect deficiencies in legal effectiveness, compliance, and risk-based regulatory enforcement. Therefore, this study recommends strengthening risk-based supervision, improving inter-agency coordination, enhancing legal sanctions, and promoting consumer legal literacy as integral measures to improve the protection of consumers’ rights to safe processed food products. This research contributes both theoretically and practically by reinforcing the application of effectiveness of law and risk-based regulation theories in the context of food safety governance.